Peran Masyarakat Dalam Pengembangan Ekowisata Subak Sembung - Putri, Kadek Julia Maharanee; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
Subak Sembung Ecotourism is a nature-based tourist attraction located in Denpasar City, Bali. This research aims to analyze the role of the community in the development of Subak Sembung Ecotourism. The data used in this research is a type of qualitative research. The data used were obtained through interview methods and literature research using previous research that still has a relationship with the research being conducted. In determining the informants, it was carried out using a purposive sampling method, namely with informants managing the Subak Sembung Ecotourism. This research uses the concept of the five main functions of society as a system in which there are economic functions, social functions, social control functions, participation functions and mutual support. The results of the research show that the community has its own role in carrying out its functions. They play an active role as farmers, stake holders, traders, community organizations and the public as consumers. The role of the community in Subak Sembung Ecotourism has been going well and is structured. Keywords : role, community, ecotourism, development, subak